Original paperTranscatheter implantation of the biological Sapien Edwards valve in the pulmonary position – first experiences - Demkow, Marcin; Rużyłło, Witold; Biernacka, Elżbieta Katarzyna; Kowalski, Mirosław; Śpiewak, Mateusz; Olivecrona, Göran; Hoffman, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
We present the first in Poland, and among the first in Europe, cases of transcatheter implantation of the biological Sapien Edwards valve in the pulmonary position. The valves were implanted successfully without periprocedural complications in 2 patients with postoperative right ventricular outflow tract dysfunction.